Asparagine Synthetase-Mediated l-Asparagine Metabolism Disorder Promotes the Perineural Invasion of Oral Squamous Cell Carcinoma - Fu, Yong; Ding, Liang; Yang, Xihu; Ding, Zhuang; Huang, Xiaofeng; Zhang, Lei; Chen, Sheng; Hu, Qingang; Ni, Yanhong (Frontiers in Oncology, 2021)
Dysregulated amino acids metabolism reciprocally interplays with evolutionary phenotypic characteristics of cancer cells to enhance metastasis. The high metastasis potential of oral squamous cell carcinoma (OSCC) can manifest with perineural invasion (PNI). We here aimed to determine the role of amino acids metabolism in OSCCs with different PNI statuses. Targeted metabolomics was used to quantify 48 amino acids in 20 fresh OSCC samples and 25 amino acids were successfully detected, within which 9 were significantly up-regulated in PNI positive (PNI+) samples. As its highest area under the curve value (0.9063), L-asparagine was selected as the biomarker to distinguish PNI+ from PNI negative (PNI-). Then, the key enzyme of L-asparagine, asparagine synthetase (ASNS), was investigated using immunohistochemistry with 86 OSCC patients. The results showed that ASNS mainly expressed in tumor epitheliums and positively correlated with lymph node metastasis and PNI. Moreover, subgroup survival analysis revealed that ASNS expression combined with PNI status significantly improved their prognostic value, which was confirmed by the TCGA OSCC cohort (n = 279). To validate whether ASNS promotes PNI, we determined ASNS expression levels in five OSCC cell lines and one normal oral keratinocyte, and HSC3 showed the lowest ASNS level but CAL33 had the highest. Therefore, HSC3 and CAL33 (or PBS as control) were selected and injected separately into sciatic nerves to construct the in vivo PNI mouse models. Although both models eventually developed the hind-limb paralysis, nerve dysfunction in the CAL33 model progressed significantly earlier than HSC3 (Day 9 vs. Day 24). Besides, CAL33 migrated significantly farther than HSC3 in the nerve microenvironment (P = 0.0003), indicating high ASNS expression is indispensable for OSCC progression, especially PNI formation, through L-asparagine metabolism alteration. This study provides novel insights into how amino acids metabolism disorders alter tumor neurotropism which helps cancer metastasis.